Redesign of Leg Prosthetic Clamp Adapter Component Made of Aluminium Mg5085 by using CAD and CAE - Fajar Yulianto Prabowo; S Suyitno (Departemen Teknik Mesin dan Industri, Universitas Gadjah Mada, 2019)
Designing used CAD (Computer Aided Design) to create a design and analyzing the clamp adapter on the leg prosthetic component by using CAE (Computer Aided Engineering) had already been done. This research background is due to a failure on the part of the leg prosthetic component whereas the aim of this research is intended being able to design a leg prosthetic clamp adapter to be able to withstand 300kg load. Aluminium Mg 5085 is the material to make this clamp adapter then 300kg loading test is conducted. 300kg weight is chosen as considered having the average weight of adults who suffer obesity. The result showed that the hugest stress is 25.41 MPa, the biggest displacement 6.876 mm, and 0.1345mm stress. This analysis result is far lower from yield strength aluminium Mg which is 140 MPa. Hence, this design can be said safe and can be tested further.